The Effect of Student Worksheet-Assisted Project-Based Learning on Learning Outcomes and Critical Thinking in Moderation of Student Learning Motivation in Electrolytic Cell - Putra, Vahemas Aditya pamila; Dasna, I Wayan; Nazriati, Nazriati (Universitas Negeri Malang, 2023)
This study aims to discover the differences between learning outcomes and critical thinking skills between students who follow project-based Learning and conventional Learning. Second, to know the impact of project-based learning on student worksheets on learning outcomes and critical thinking in moderation of student learning motivation. The method used in the initiation is a quasi-experiment with a pretest-posttest control group design. The results show that (1) there are differences in learning outcomes between students who follow project-based learning and students who follow conventional learning; (2) there is a difference in critical thinking capabilities among students who go with project-based learning and conventional students; (3) motivation to moderate project-based learning to help students worksheets to improve student's learning outcomes; (4) motivation not to moderately project-driven Learning to help students' worksheets on critical think ability.